ANALISIS YURIDIS PENGGABUNGAN PEMIDANAAN TINDAK PIDANA LINGKUNGAN HIDUP DAN TINDAK PIDANA PENCUCIAN UANG BERDASARKAN STUDI PUTUSAN NOMOR : 71 /Pid.sus/LH/2018/PN.PLW DAN PUTUSAN NOMOR : 38/Pid.sus/LH/2018/PN.Pbr - Miftah Farhan Sitorus; Erdianto Erdianto; Tengku Arif Hidayat (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
The convict M. Ali Honopiah received two court decisions that occurred inthe case in Decision Number: 71/Pid.Sus/Lh/2018/Pn Plw and Decision Number:38/Pid.Sus-TPK/2018/PN.Pbr ., So that the convict commits several criminal acts atonce, namely the Commerce and Transport of Protected Animals and the Crime ofMoney Laundering. From the two decisions above, that the convict committed severalcriminal acts at different times so that the two decisions were not in accordance withArticle 65 of the Criminal Code.The purpose of writing this thesis, namely: First, to find out the juridicalperspective on the merger of Environmental Crimes and Money Laundering, theStudy of Decision Number 71/Pid.Sus/Lh/2018/Pn Plw and Decision Number38/Pid.sus/LH/ 2018/Pn.Pb. Second, to find out the application of the merger ofEnvironmental Crimes and Money Laundering, the Study of Decision Number71/Pid.Sus/Lh/2018/Pn Plw and Decision Number 38/Pid.sus/LH/2018/Pn.pbr.This type of research can be classified into normative research. The datasources used are primary data and secondary dataFrom the results of the study that in the decision on environmental crimes andmoney laundering crimes committed by M Ali Honopiah. In this case, the PublicProsecutor (JPU) stated that M. ALI HONOPIAH has been legally proven and guiltyof committing the crime of money laundering. because the elements of a criminaloffense in the Primary indictment have been fulfilled in themselves and the actions ofthe Defendant. So that the decision has not used Article 65 regarding the merging ofpunishmentsKeywords: COMMERCIAL CRIMINAL ACTS OF ENVIRONMENTAL CRIMINALACTS OF MONEY LAUNDERING